USE OF FUZZY LOGIC TO OPTIMIZE FERTILIZER APPLICATION IN THE RADISH - Godinho, Emmanuel Zullo; Caneppele, Fernando de Lima; Gasparotto, Hélio Vagner (Revista Brasileira de Engenharia de Biossistemas, 2021)
The aim of this study was to develop a fuzzy-rules-based model to evaluate the effects caused by varying the dosages of two soil fertilizers (mineral and organic) on root diameter. Fuzzy logic is a method that presents a language, more appropriate to everyday life, as the sky is cloudy. For the input variables of this system, mineral and organic fertilizers were used, for the output the root diameter, in cm. After optimizing the input rules, it can be seen that for the application of fertilizers (mineral and organic) the best dosages were 15 to 60 and 20 to 60 g m-2, respectively. With this application of fuzzy rules in real data, these benefits can be taken to those involved in the radish production chain, thus resulting in a reduction in product dosages and improving its final profitability.